Modeling, experimental trials, and design space determination for the GEA ConsiGma™ coater. Issue 4 (12th March 2019) - Kemp, Ian C.; Iler, Lewis; Waldron, Michael; Turnbull, Neil
ABSTRACT: A mechanistic model was developed for tablet coating and applied successfully to the novel GEA ConsiGma™ coater. The majority of the heat for evaporation is supplied by conduction from the tablet bed rather than convection from the hot gas. Tablet drying depends strongly on exhaust air and bed temperatures and weakly on spray rate. A trapezoidal design space was predicted and verified by experiments at different scales, achieving good quality coated tablets over a wide range of operating conditions. The ConsiGma™ achieves many more coating passes per tablet than a batch coater despite its much shorter cycle time, giving excellent color uniformity.